Determination of the mechanism of sorption of Cu2+ ions to hydrolyzed fibroin - Eshchanov, Khushnudbek (International Journal of Advanced Chemistry, 2022)
We were able to obtain hydrolyzed fibroin with sorbing properties from fibrous silk waste. We determined the mechanism of sorption of Cu2+ ions into hydrolyzed fibroin using the Dubinin-Radushkevich isotherm. Physical sorption of Cu2+ ions to hydrolyzed fibroin has been shown to be predominant. However, it has been observed that the colour of hydrolyzed fibroin, which sorbs Cu2+ ions, changes to yellow over time. Analysis of the yellowed sample by IR spectroscopy showed that Cu2+ ions formed a coordinate bond with the hydrolyzed fibroin.Â Â